2022
DOI: 10.3389/fendo.2021.814074
|View full text |Cite
|
Sign up to set email alerts
|

The Urinary Glucose Excretion by Sodium–Glucose Cotransporter 2 Inhibitor in Patients With Different Levels of Renal Function: A Systematic Review and Meta-Analysis

Abstract: ObjectivePrevious evidence suggested that sodium–glucose cotransporter 2 inhibitor (SGLT2i)-mediated urinary glucose excretion (UGE) appeared to be reduced with a decrease in glomerular filtration rate. Thus, we conducted a systematic review and meta‐analysis to compare SGLT2i-mediated UGE among individuals with different levels of renal function.MethodsWe conducted systematic searches in PubMed, Medline, Embase, Cochrane Central Register of Controlled Trials, and ClinicalTrial.gov from inception to May 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
1
11
1
Order By: Relevance
“…Conversely, the lower the GFR, the smaller is the glycosuria. Anyway, it was found that the inhibition towards renal glucose reabsorption was constant across all levels of renal function, indicating that, regardless of GFR, inhibition of glucose reabsorption might reach its maximum [ 16 ]. Accordingly, an average of 0.79% reduction in HbA1c is obtained in normal renal function, 0.3–0.4% in the estimated GFR (eGFR) range of 30–59 mL/min/1.73 m 2 , until the total ineffectiveness when the parameter is less than 30 mL/min/1.73 m 2 [ 17 ].…”
Section: The Anti-hyperglycemic Effect Of Sglt2-ismentioning
confidence: 99%
“…Conversely, the lower the GFR, the smaller is the glycosuria. Anyway, it was found that the inhibition towards renal glucose reabsorption was constant across all levels of renal function, indicating that, regardless of GFR, inhibition of glucose reabsorption might reach its maximum [ 16 ]. Accordingly, an average of 0.79% reduction in HbA1c is obtained in normal renal function, 0.3–0.4% in the estimated GFR (eGFR) range of 30–59 mL/min/1.73 m 2 , until the total ineffectiveness when the parameter is less than 30 mL/min/1.73 m 2 [ 17 ].…”
Section: The Anti-hyperglycemic Effect Of Sglt2-ismentioning
confidence: 99%
“…13 The magnitude of SGLT2 inhibitor-mediated glycosuria is reduced in chronic kidney disease. 14,15 Two-thirds of the filtered sodium is absorbed in the proximal tubule, 16 primarily through the action of NHE3 (sodium-hydrogen exchanger 3). NHE3 is colocalized with and structurally interlinked with SGLT2 in the brush border.…”
Section: Effects Of Sglt2 Inhibition In the Proximal Renal Tubule And...mentioning
confidence: 99%
“…They efficiently lower blood glucose levels by inhibiting renal SGLT2, a Na + -dependent glucose transporter which normally accomplishes complete glucose reabsorption along with SGLT1, another isoform that is not inhibited by specific SGLT2 inhibitors (33)(34)(35). As a consequence, the patients excrete more glucose in their urine (36,37). Recent large clinical studies of high quality have unequivocally proven that SGLT2 inhibition has further significant and diabetes-independent cardio-and nephroprotective effects that are, in many aspects, regarded as a milestone in cardiology and nephrology (38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%